Design and evaluation of trading strategy in a-Trader system - Korczak, Jerzy; Hernes, Marcin; Bac, Maciej (Business Informatics, 2014)
The article presents an approach to the performance analysis of trading strategies in the a-Trader system. A-Trader supports investment decisions on the FOREX market. The first part of the article contains a description of the a-Trader system from the user viewpoint. Next, the algorithms of the selected agents’ strategies are presented. In the last part of the article, the performance evaluation of strategies is proposed and illustrated
Informatyka Ekonomiczna = Business Informatics, 2014, Nr 3 (33), s. 88-101
Keywords: multi-agent systems; financial decisions; FOREX; investment strategies; systemy wieloagentowe; decyzje finansowe; strategie inwestycyjne